N, S co-doped Co3O4 core–shell nanospheres with high peroxidase activity for the fast colorimetric detection of catechol. Issue 44 (4th November 2021) - Liu, Xiangwei; Cao, Xiaoyan; Zhao, Shuang; Liu, Zhenxue; Lu, Guang; Liu, Qingyun
Abstract : A fast colorimetric catechol sensing platform is constructed on the basis of the enhanced peroxidase-like activity of N, S co-doped Co3 O4 core–shell nanospheres, ascribed to the active species including ˙O2 − and h + . Abstract : It is necessary to develop nanoperoxidases with high activity to construct a fast and cheap sensing platform for real-time detection of some pollutants. In this study, the as-prepared N and S co-doped core–shell cobaltosic oxide nanospheres (N, S-Co3 O4 ) exhibit excellent peroxidase-like activity. The oxidation reaction of the colorless chromogenic substrate TMB by H2 O2 is used to evaluate the peroxidase-like behaviors of N, S-Co3 O4 . As expected, the N, S-Co3 O4 nanospheres accelerated the oxidation of TMB accompanied by a blue shift only in 1 min. Thus, the N, S-Co3 O4 nanoperoxidase exhibits high affinity towards TMB ( K m = 0.072 mM) and H2 O2 ( K m = 3.78 mM). Moreover, as the catalytic process of N, S-Co3 O4 can be inhibited in the presence of catechol, a fast inexpensive colorimetric sensor of catechol with high sensitivity and good selectivity was constructed. The enhanced catalytic activity of N, S-Co3 O4 is attributed to some active species, including h + and ˙O2 −, owing to the more active sites on N, S-Co3 O4 . The colorimetric method has been validated by detecting catechol in real water samples for practical application.